Trends in Formulation of Night Cream Containing Essential Oil - Isnaini, Nadia; Faradhila, Jihan; Maysarah, Hilda; Prajaputra, Vicky; Harnelly, Essy; Zulkarnain, Zulkarnain; Maryam, Siti; Muhammad, Syaifullah; Haditiar, Yudi; Desiyana, Lydia Septa; Sari, Febia (Journal of Patchouli and Essential Oil Products, 2023)
Night creams play a pivotal role in skincare routines by safeguarding against nocturnal moisture loss and promoting a smooth, wrinkle-free complexion. However, conventional formulations of night creams often incorporate synthetic active substances, potentially leading to adverse effects over prolonged use. Addressing this concern involves substituting these synthetic compounds with natural ingredients, particularly essential oils, renowned for their diverse skincare benefits encompassing anti-acne, anti-aging, anti-wrinkle, and moisturizing properties. A systematic review was conducted to establish a foundation for future investigations, focusing on the integration of essential oils in night cream formulations. The outcomes revealed that various night cream formulations, enriched with essential oils derived from natural ingredients such as rosemary oil, camellia oil, clove oil, geranium oil, lemongrass oil, rosehip oil, and sandalwood oil, demonstrate remarkable efficacy in preserving skin moisture. The versatility of essential oils has been showcased in the development of night creams, boasting diverse beneficial effects across skincare concerns. This systematic investigation highlights the potential of essential oil-based night creams, which have recently gained traction in the global market. The burgeoning introduction of these products signifies an escalating demand for such skincare solutions and points towards promising prospects for future advancements in essential oil-based night creams.Keywords: essential oils, formulation, natural product chemistry, night cream, patchouli oil, skincare